Development of Problem-Based Learning-Based Student Worksheets to Improve Elementary School Student Learning Outcomes - Egatri, Dewi; Nurlaksana Eko Rusminto; Siti Samhati; Sunyono (LJPI UI Bunga Bangsa Cirebon, 2025)
Objective: This study aims to develop a Problem-Based Learning (PBL)-based Student Worksheet (LKPD) on the topic of words and syllables to improve the learning outcomes of third-grade students in Indonesian language learning. Novelty: The developed LKPD integrates the PBL approach into Indonesian language lessons, offering an innovative learning medium tailored for elementary school students. Methods: The research used a Research and Development (R&D) design with the 4D model (Define, Design, Develop, and Disseminate). Subjects included 20 experimental and 20 control class students each from SDIT Harapan Bangsa, SDIT Rasyid Sedayu, and SD Negeri 1 Merak Batin. Data were collected through questionnaires, observations, tests, and documentation, then analyzed using descriptive quantitative and qualitative methods. Results: Expert validation showed high feasibility, with scores of 89.3 (material expert), 98 (media expert), and 76 (language expert), averaging 87.76 (very valid). Practicality tests yielded an average of 92 from teachers and 94 from students (both very practical). The N-Gain test indicated moderate effectiveness: 0.68 (SDIT Harapan Bangsa), 0.67 (SDIT Rasyid Sedayu), and 0.65 (SD Negeri 1 Merak Batin). The independent t-test showed a significance value of 0.000 < 0.05, confirming a significant difference between control and experimental classes. Conclusions: The PBL-based LKPD on words and syllables is highly valid, very practical, and moderately effective, making it a promising innovative medium to enhance elementary students’ learning outcomes.